ISLAM AND THE MORAL ECONOMY: THE CHALLENGE OF CAPITALISM - Sumiyana . (Journal of Indonesian Economy and Business (JIEB), 2014)
This is a book review on Islam and the moral economy that highlights the challenge of capitalism.